Official secrets what the Nazis planned, what the British and Americans knew - Breitman, Richard 1947- (Hill & Wang, 1998)
"In the course of its war for world domination and a projected racial utopia, Hitler's government committed monstrous crimes. As defeat neared, the Third Reich's officials tried to destroy all the physical and documentary evidence about their murder of millions. They did not fully succeed, but huge gaps in the historical record have made it hard for us to reconstruct how they planned the Holocaust." "Great Britain already had some of the evidence, however, for, all along, its intelligence services had been intercepting, decoding, analyzing, and circulating many German police radio messages and some from the SS. Yet this critical evidence was sealed away - marked "Most Secret," "To Be Kept under Lock and Key," and "Never to Be Removed from This Office" - and it has only now reappeared." "Integrating this new evidence with the known sources, Richard Breitman examines how Germany's leaders brought about the Holocaust - and when. He assesses the British and American suppression of information about Nazi killings, and the tensions between the two powers over how to respond. His work concludes with an examination of the consequences (including the failure to punish many known war criminals) of keeping this information secret for so many decades."--BOOK JACKET.